Pregnancy and Delivery Management in Women with Adenomyosis and Prevention of Gestational Complications (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Over recent years, there has been a growing interest in exploring the relationship between adenomyosis and unfavorable pregnancy outcomes in the field of reproductive medicine. The aim of this study is to assess various strategies for managing pregnancy in women with adenomyosis to mitigate the risk of gestational complications. Our findings underscore the need for a tailored approach to pregnancy care and thorough preconception preparation to enhance maternal and fetal outcomes.